Simulating Tissue Donor T Cell Responses in SCT - Vishal Koparde; Badar Abdul Razzaq; Tara Suntum; roy sabo; Allison Scalora; Myrna Serrano; Max Jameson-Lee; Charles E Hall; David Kobulnicky; Nihar Sheth; Juliana Feltz; Daniel Contaifer Jr.; et al. (Open Science Framework, 2022)
Dynamical System Modeling to Simulate Donor T Cell Response to Whole Exome Sequencing-Derived Recipient Peptides: Understanding Randomness In Alloreactivity Incidence Following Stem Cell Transplantation
Keywords: Alloreactivity; Antigen presentation; Donor T cell; Dynamical systems; Graft versus host disease; HLA Antigen presentation; HLA binding affinity; minor histocompatibility antigens; Randomness in clinical outcome; Stem cell transplantation; Stochastic; T cell antigen response simulation; Tissue antigen expression; Vector - Operator Matrices; Whole exome sequencing